Analisis Asas Legalitas dalam Kewenangan Presiden Menunda Eksekusi Hukuman Mati Terpidana Mary Jane Veloso - Fiddin, Mohamad Fahmi; Karli, Karli (FOCUS, 2023)
Clemency is very important for the government of a country because it can reduce the risks arising from a judge's decision, especially for maximum punishment such as death penalty, which allows the execution of innocent people. Problems arise when a death row convict asks for clemency and the President rejects it. However, when the executions were to be carried out, the President issued an order to postpone the executions, causing legal uncertainty regarding the denial of clemency. As a result, law enforcement on narcotics crimes becomes ineffective. This happened when the execution of Mary Jane Veloso was postponed. In this study, delaying the implementation of decisions that have permanent legal force through clemency is not a legal remedy, but it is the right of the Head of State to grant pardons to citizens who have been sentenced by a court. Apart from that, there is a legality principle in the presidential policy in delaying the execution of convict Mary Jane Veloso which has been regulated in Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia and Law Number 1 of 2006 concerning Mutual Assistance. In Criminal Matters and Law Number 15 of 2008 concerning Ratification of the Treaty On Mutual Legal Assistance in Criminal Matters (Agreement on Mutual Assistance in Criminal Matters). Setting the provisions of the law is an effort to realize the principle of checks and balances, so that the use of this authority has been limited, that is, before the President decides to grant a postponement of the execution of the death penalty, the President must first obtain consideration from the Supreme Court.